Identification of physical changes in dome house (Teletubies) Ngelepen Dusun, Prambanan with the Post Occupancy Evaluation (POE) approach - Budiharjo, Rachmat; Leksono, Soesilo Boedi (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2024)
A relocation of houses for the residents of Sengir hamlet, approximately 500 meters away from Nglepen hamlet, which was affected by the earthquake in 2006, the Dome House (Teletubbies) is the product of the participation of several donor countries and is located in Nglepen hamlet, Sumberharjo Village, Kapanewon Prambanan, Sleman Regency, Special Region of Yogyakarta. It has caused its people many contentious issues since it was first used in April 2007. In 2016, the region received the nickname